Antibiotic Resistance and Public Knowledge - Duarte, Ana (2024)
The discovery of antibiotics was one of the most landmark discoveries of the twentieth century, but their inappropriate use fostered the development of resistant bacteria, thus becoming a threat to public health. In Portugal, the population’s literacy on this subject is not known, and as such, a study was carried out to assess the knowledge of the population in the central interior region and to assess adherence to antibiotic therapy. The results showed that the main reason for the use of antibiotics is the treatment of diseases of the respiratory tract and that the younger population is the one with the highest level of education, but it is not reflected in health literacy. It was also found that although less than half of the respondents know what antibiotic resistance is, most have a moderate to high level of adherence to antibiotic therapy.Keywords: resistance, antibiotics, therapeutics, pharmaceutical.